PROSPECTS FOR ESTABLISHING THE RIGHTS OF PERSONS WHO HAVE REPORTED CORRUPTION OFFENSES IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Management and Law, 2024)
This article analyzes the prospects for establishing the basic rights of persons who have reported corruption offenses.